2016
DOI: 10.1088/1361-6463/50/1/015210
|View full text |Cite
|
Sign up to set email alerts
|

Geometry optimization of linear and annular plasma synthetic jet actuators

Abstract: The Electro-Hydro-Dynamic (EHD) interaction induced in atmospheric-pressure air by a surface Dielectric Barrier Discharge (DBD) actuator has been experimentally investigated. Plasma Synthetic Jets Actuators (PSJAs) are DBD actuators able to induce an air stream, perpendicular to the actuator surface. These devices can be used in the aerodynamics field to prevent or induce flow separation, modify the laminar to turbulent transition inside the boundary layer, and stabilize or mix air flows. They can also be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 50 publications
1
23
1
Order By: Relevance
“…1b. This counter wind collides with the main flow and defects wind in the vertical direction to the dielectric surface when there is no gap between each actuator module, as in the case of so-called plasma synthetic jet actuators 22 . The generation of the counter ionic-wind due to the cross-talk phenomenon is undesirable in view of the multiplied acceleration of ionic wind by successive actuator modules.…”
Section: Introductionmentioning
confidence: 99%
“…1b. This counter wind collides with the main flow and defects wind in the vertical direction to the dielectric surface when there is no gap between each actuator module, as in the case of so-called plasma synthetic jet actuators 22 . The generation of the counter ionic-wind due to the cross-talk phenomenon is undesirable in view of the multiplied acceleration of ionic wind by successive actuator modules.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of device has been fabricated using Printed Circuit Boards because this decreases the manufacturing cost and weight. Two electrodes are required [ 164 , 165 , 166 , 167 , 168 , 169 ]: one of them for high-voltage and second one for the ground. These electrodes are fabricated on opposite sides of the PCB substrate, in which the insulation layer is FR4 and the dielectric breakdown voltage is determined by that material, about 50 kV.…”
Section: Printed Circuit Boards For Biomedical Applicationsmentioning
confidence: 99%
“…The advantage of the plasma synthetic jet actuators is acceptable power consumption (order of 100 W) [66]. The experimental results of Neretti et al [68] indicated that the annular plasma synthetic jet actuator exhibits better performance than the linear version.…”
Section: Refmentioning
confidence: 99%